Surface modification of injectable PDLLGA microspheres as stem cell delivery systems for tissue repair applications - Baki, Abdulrahman (2017)
Successful tissue repair requires orchestrating a range of biochemical and biophysical factors to direct cell differentiation towards tissue specific lineages. Biodegradable poly DL lactic acid-co-glycolic acid (PDLLGA) microspheres have been reported as a promising injectable cell delivery system with controllable growth factor release potential for different tissue engineering applications. Injectable PDLLGA microspheres have been shown to form highly porous scaffolds at body temperature with a mechanical strength comparable to bone tissues. However, as the elastic properties of the injury microenvironment were shown to have a pivotal role on directing stem cell lineage specification, this work has proposed photo-crosslinkable gelatine methacrylate (gel-MA) hydrogels as promising surface coatings with tunable elastic properties. Moreover, as PDLLGA microspheres have limited functional groups on their surface, this work has evaluated different surface modification and grafting approaches to enable proper grafting of thick gel-MA hydrogel layer to the surface. Surface adsorption, surface entrapment, and oxygen plasma treatment approaches have been proposed and evaluated to modify the surface of PDLLGA microspheres with high density of gel-MA molecules. Surface analytical techniques such as ToF SIMs and XPS have been used to evaluate and quantify the density of gel-MA molecules on the surface, while fluorescent and scanning electron microscopies have been used to visualise the fluorescent deposition of fit-C gel-MA to the surface. Later, grafting-to and encapsulation approaches have been investigated to graft a thick layer (10-20 μm thick) of gel-MA hydrogel to the surface of PDLLGA microspheres following modification with gel-MA. Fluorescein isothiocyanate labelled human serum albumin Fit-C HSA has been loaded into PDLLGA microspheres as a model protein to study its release behaviour from the proposed system. Release data have shown a comparable release profile between PDLLGA microspheres before and after coating with the hydrogel layer suggesting no adverse effect of the proposed coating approach on the release behaviour. Gel-MA hydrogels with tunable elastic properties have been prepared and analysed using texture analyser and atomic force microscopy (AFM). Hydrogels have been later imaged with focused ion beam scanning electron microscope (FIB-SEM) using a novel approach to capture the hydrated structure of the hydrogel. Data obtained from the texture analyser using the compression and indentation mode tests have shown that the elastic modulus values were significantly higher than the values obtained from tension mode tests. In comparison, the values obtained from the texture analyser with the tension mode test were comparable with the values obtained using the AFM nano-indentation tests. This has been explained with the poroelastic behaviour of the hydrated hydrogel structure where a micron size pores have been observed. To verify findings, human mesenchymal stem cells have been cultured on the surface of gel-MA hydrogels to study their phenotypic behaviour and stained with anti-osteogenic or anti-neurogenic immunofluorescent markers to define their fate accordingly. Images have shown that cells cultured on hydrogels with AFM analysed elastic values of (~26, ~9.3, and ~0.1 KPa) have committed to a phenotypic behaviour related to the elastic modulus values of bone, muscle, and neuronal tissues respectively. In comparison, the elastic modulus values obtained from gel-MA hydrogel microbeads with AFM have been notably higher and appeared to be dependent on the cross-linking temperatures. Finally, the proposed cell delivery system can be used to control the chemical and the mechanical properties of the stem cell microenvironment which may pave the way towards directing stem cell differentiation into tissue specific cell lineages for different tissue repair applications.